Alkynylation of graphene via the Sonogashira C–C cross-coupling reaction on fluorographene. Issue 8 (8th January 2019) - Chronopoulos, Demetrios D.; Medved', Miroslav; Błoński, Piotr; Nováček, Zdeněk; Jakubec, Petr; Tomanec, Ondřej; Bakandritsos, Aristides; Novotná, Veronika; Zbořil, Radek; Otyepka, Michal
Abstract : We report successful grafting of alkynyl groups onto graphene via the Sonogashira reaction between fluorographene and terminal alkynes. Abstract : We report successful grafting of alkynyl groups onto graphene via the Sonogashira reaction between fluorographene and terminal alkynes. Theoretical calculations revealed that fluorographene can efficiently bind and oxidize the palladium catalyst on electrophilic sites activated by fluorine atoms. This paves the way towards conductive and mechanically robust 3D covalent networks.